Diagnosing the reality of the organizational genetic fingerprint (DNA) of Iraqi business organizations - exploratory and analytical research in a sample of Iraqi organizations - Muayid Al-Saedy; Janan Mahdi Al-dhan (Iraqi Journal for Administrative Sciences, 2025)
The research aims to diagnose the reality of the organizational genetic fingerprint (DNA) in a sample of Iraqi organizations as a set of elements and factors represented in decision-making rights, information, motivators, organizational structure, which are determined by certain characteristics that contribute, through their interaction and integration with each other, in determining the organization’s personality and identity, through the reality The prevailing understanding of the organizational genetic fingerprint (DNA) in a number of different Iraqi business organizations in the nature of their industry, represented by Al-Rashid Bank, Al-Hussein Hospital, and the College of Administration and Economics) after a random sample of (66) people was selected from it, all of which are located in the city of Karbala, and their opinions were polled. According to a global questionnaire prepared for this purpose, non-parametric statistical analysis and processing tools were chosen appropriate for analyzing and testing the research hypotheses. The research came to the conclusion that there is a clear understanding of the components of the genetic fingerprint by the targeted sample, and that there is no discrepancy in the organizations sample’s awareness of the components. Genetic fingerprinting